Regularities of Physical Processes in Hybrid Solid-Propellant Rocket Engines - Bondarchuk S. S. Sergey Sergeevich; Vorozhtsov A. B. Aleksandr Borisovich; Zhukov A. S. Aleksandr Stepanovich; Borisov B. V. Boris Vladimirovich (2015, 2015)
Title screen